Titanate nanotubes: towards a novel and safer nanovector for cardiomyocytes. Issue 6 (September 2012) - Papa, Anne-Laure; Dumont, Laure; Vandroux, David; Millot, Nadine
Abstract Actively contractile cardiomyocyte (CM) monolayer represents an interesting tool to study both cardiac diseases and injuries. However, this model is poorly transfectable with conventional agents. Consequently, there is a need to develop new carriers that could overcome this problem. Titanate nanotubes (TiONts) could be a potential candidate due to possibly higher cell uptake as a direct consequence of their shape. On the basis of this rationale, TiONts were assessed for their cytotoxicity and internalization pathways. Cytotoxicity was assessed for TiONts either functionalized with PEI or unfunctionalized and its spherical counterpart P25 TiO2. No cytotoxic effect was observed under TiONts, TiONts-PEI1800 and P25 TiO2 exposed conditions. The tubular morphology was found to be an important parameter promoting internalization while reversing the charge was assessed as non-additional. Internalization was found to occur by endocytosis and diffusion through the membrane. A preliminary transfection study indicated the potential of TiONts as a nanocarrier.